Evaluation of possible integration of solar chimney power plants with high-rise buildings: A numerical analysis. (15th November 2022) - Saad, Muhammad; Ahmed, Naveed; Giovannini, Lorenzo; Mahmood, Mariam; Rafi, Muhammad U.; Qaisrani, Mumtaz A.
Abstract: The application of Solar Chimney Power Plants (SCPPs) has remained restricted to arid regions, and the construction of chimneys with great heights poses a barrier to their widespread usage. The current study investigates a hybrid approach integrating SCPPs with high-rise buildings, one step closer to sustainable buildings that utilize renewable energy sources for power needs. Numerical simulations were conducted to investigate the effect of reducing the collector area on flow behavior and power output. First, the numerical model was validated against the experimental data from the SCPP's pilot plant in Manzanares. A detailed analysis was then performed to investigate the effect of reducing the collector area. The ensuing results depict that reduction in collector angle disrupts the symmetry of the flow resulting in reduction and deflection of the peak velocity near the base of the chimney. A threshold of 120° collector angle is found below which a strong swirling flow is detected inside the whole chimney tower, with a drop in the plant's velocity, pressure, and temperature rise. Moreover, the results indicate that reducing the collector angle from 360° to 120° decreased the power output from 47.4 kW to 26.1 kW. The hybrid SCPP design aims to ease the construction of large chimneys in new high-rise buildings and proposes quantitative information on the plant's performance when the collector area is reduced because of scarce land resources in urban areas. Highlights: Application of solar chimney power plants in urban areas by integration with high-rise buildings is investigated numerically. Below 120° of the collector angle, strong swirls are detected inside the whole chimney tower. A deflection in the flow pattern inside the chimney is observed with the reduction of the collector angle. The power output is decreased from 47.4 kW to 26.1 kW in response to the reduction of the collector angle from 360° to 120°.